Improvement in oral health and compliance in a child with congenital hypothyroidism : case report = Progreso del cuidado oral y el comportamiento en un niño con hipotiroidismo congénito : reporte de caso - López Santacruz, Hiram Daniel
Congenital hypothyroidism is a metabolic disorder that requires special health care interventions. It has influence in overall growth and oral conditions in pediatric patients, and also can affect child cooperation during dental treatment because this metabolic condition is the most common preventable cause of mental retardation. The aim of this paper is to report the dental treatment of a child with congenital hypothyroidism who is four years and five months old, with many facial and oral characteristics of the metabolic condition, including severe early childhood caries and malocclusion. At first, it was observed a lack of cooperation of the patient with speech and learning impairment, but with the help of the Pedagogy team at the Pediatric Dental Clinic Playroom, he developed confidence and diminished anxiety every appointment. We present the follow-up during 15 months, where we could observe favorable outcomes in oral health and compliance of the child.